Assessment of Health Technologies: A Hospital Approach for the Incorporationof Medical Devices - Lizcano-Jaramillo, P. A.; Camacho-Cogollo, J. E. (Revista Mexicana de Ingenieria Biomedica, 2019)
This article presents the state of the art about the evaluations of technology and the contributions that have been made at a hospital level in different countries of the world. The incorporation of health technologies is focused on the improvement of quality and efficiency in the provision of health services. The evaluation of technology is a scientific, multidisciplinary and multidimensional process that aims to contribute and improve decision making in the procedures of acquisition and technological incorporation, through the comparative evaluation of the positive and negative effects of technologies in hospitals. The purpose generally considers various alternatives, providing the best selection of technology that compensates for medical needs in health institutions. At the global level, they have constantly worked to improve the technology assessment processes at the national and hospital levels. The implementation of evaluation methodologies in hospitals allows contributing to the reduction of the risks gene-rated using medical devices or equipment in relation to patient safety by implementing effective technologies for various treatments. In conclusion, the technology assessment is a fundamental process that provides relevant in-formation for decision making for the incorporation of new medical devices in hospitals.